2021
DOI: 10.1371/journal.pone.0260315
|View full text |Cite
|
Sign up to set email alerts
|

Detection of overdose and underdose prescriptions—An unsupervised machine learning approach

Abstract: Overdose prescription errors sometimes cause serious life-threatening adverse drug events, while underdose errors lead to diminished therapeutic effects. Therefore, it is important to detect and prevent these errors. In the present study, we used the one-class support vector machine (OCSVM), one of the most common unsupervised machine learning algorithms for anomaly detection, to identify overdose and underdose prescriptions. We extracted prescription data from electronic health records in Kyushu University Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…"Overdosage" was then the most frequently class of DRPs associated to recommendations observed in this study. Similar results have been shown in previous research [9,[13][14][15][16][17][18][19][20]. Bedouch et al [9] for example reported 19.2% of supratherapeutic doses.…”
Section: Discussionsupporting
confidence: 90%
“…"Overdosage" was then the most frequently class of DRPs associated to recommendations observed in this study. Similar results have been shown in previous research [9,[13][14][15][16][17][18][19][20]. Bedouch et al [9] for example reported 19.2% of supratherapeutic doses.…”
Section: Discussionsupporting
confidence: 90%
“…Eleven articles (84.6%) were published between 2020 and 2023. The training datasets used were very heterogeneous: the length of study varied from 2 weeks14 to 7 years15; the number of prescription orders analysed went from 3116 to 5 804 192 17…”
Section: Resultsmentioning
confidence: 99%
“…Eight publications14 15 17–19 23 24 26 used supervised ML models (online supplemental table 1); unsupervised ML algorithms (online supplemental tale 2) were used in three publications 16 20 25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing trend to study how machine learning (ML) tools can be used to augment medical professionals’ decisions concerning diagnosis, treatment safety, and quality of patient care 4 10 . Several pharmaceutical studies 11 – 15 have applied ML to find anomalous prescriptions but not tailored to RT. In RT, several studies 16 – 19 have used ML to look at the treatment parameters to detect errors in treatment plans, but did not focus on prescription error detection.…”
Section: Introductionmentioning
confidence: 99%